The readable people of George Meredith - Wilt, Judith, 1941- (Princeton legacy library., 1975)
Meredith's reputation as an ""unreadable"" novelist prompted Judith Wilt to examine the relationship between author and reader in Meredith's fiction-a relationship that was combative and teacherly and, she contends, a central aspect of his art. Meredith was concerned with ""readable people, "" by whom he meant his readers (as he imagined them and as they were), his characters (as he created them and as they were perceived), and himself. Focusing on Meredith's struggle to shape and change the reader, Judith Wilt examines five novels: The Ordeal of Richard Feverel, Sandra Belloni, The Egoist, On.